2008
DOI: 10.1007/s12098-008-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal thrombocytopenia associated with maternal pregnancy induced hypertension

Abstract: Premature and low birth weight neonates born to mothers with pregnancy induced hypertension would require scrutiny for thrombocytopenia during early neonatal period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 9 publications
(11 reference statements)
0
6
0
Order By: Relevance
“…Pritchard et al have shown that in neonates of mothers with preE, the incidence of neonatal thrombocytopenia varies widely from 9.2 to 36%. 8 16 In another study, the incidence of thrombocytopenia associated with this disorder has been estimated at 1 per 100 live births, and it is more likely to occur in preterm and low-birth-weight infants. 13 Furthermore, several studies have also shown a prevalence of thrombocytopenia in 1 to 5% of all newborns born to mothers with preE; however, the prevalence varies depending upon the population studied.…”
Section: Incidence and Prevalence Of Neonatal Thrombocytopeniamentioning
confidence: 99%
See 1 more Smart Citation
“…Pritchard et al have shown that in neonates of mothers with preE, the incidence of neonatal thrombocytopenia varies widely from 9.2 to 36%. 8 16 In another study, the incidence of thrombocytopenia associated with this disorder has been estimated at 1 per 100 live births, and it is more likely to occur in preterm and low-birth-weight infants. 13 Furthermore, several studies have also shown a prevalence of thrombocytopenia in 1 to 5% of all newborns born to mothers with preE; however, the prevalence varies depending upon the population studied.…”
Section: Incidence and Prevalence Of Neonatal Thrombocytopeniamentioning
confidence: 99%
“…Backes et al have demonstrated that preE affects the fetus and newborn in several ways. 7 8 These effects include an increased risk of fetal demise or stillbirth; increased neonatal mortality and morbidity; IUGR; premature birth; hematological abnormalities, such as thrombocytopenia, polycythemia, and neutropenia; necrotizing enterocolitis (NEC); bronchopulmonary dysplasia; adverse neurodevelopmental outcomes and fetal origin of adult disease states. 7 8 The purpose of this article is to review neonatal thrombocytopenia as a consequence of preE, its pathogenesis, and management.…”
Section: Consequences Of Preeclampsia In the Newbornmentioning
confidence: 99%
“…The risk of thrombocytopenia is significantly increased in neonates with body weight <1500 g than those with body weight >1500 g 23,28 . Our findings corroborate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombocytopenia was also higher in the study group, but not statistically significantly (42.9% vs. 40.3%). Different incidences of thrombocytopenia have been reported, up to as much as 36% by Bhat et al [24].…”
Section: Discussionmentioning
confidence: 99%